2021
DOI: 10.18203/2320-6012.ijrms20210882
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant immunophenotypic expressions in acute lymphoid leukemia: an observational analytical study

Abstract: Background: This study aims to find out the expression of aberrant immunophenotypic markers in acute lymphoid leukemia (ALL) and to co-relate its expression with cytogenetic and molecular data.Methods: Retrospective cum prospective study was carried out in 75 patients of ALL who presented to Apollo Gleneagles hospitals, Kolkata from January 2014 and March 2019. Flow cytometry analysis was done using FC500 (Beckman coulter) All cases were classified according to latest WHO classification.Results: Out of 75 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Overall, we observed the expression of CD13 in 21.8% of the B‐ALL patients, CD33 in 19.7% of the B‐ALL patients, and CD117 in 4.7% of the B‐ALL patients. The authors from high‐income and low‐income countries reported the aberrant expression of myeloid marker expression including 10.5%–54.5% CD13, 2.6%–89% CD33, and 0%–26.2% CD117 38,39,60,62–75 . These differences in frequencies of expression of various myeloid markers might be attributed to the inherent genetic differences among ethnic subpopulations, technical factors such as lack of uniformity in using monoclonal antibody clone type, and differences in flow cytometry methodology, processing, and data analysis 74,76 .…”
Section: Discussionmentioning
confidence: 99%
“…Overall, we observed the expression of CD13 in 21.8% of the B‐ALL patients, CD33 in 19.7% of the B‐ALL patients, and CD117 in 4.7% of the B‐ALL patients. The authors from high‐income and low‐income countries reported the aberrant expression of myeloid marker expression including 10.5%–54.5% CD13, 2.6%–89% CD33, and 0%–26.2% CD117 38,39,60,62–75 . These differences in frequencies of expression of various myeloid markers might be attributed to the inherent genetic differences among ethnic subpopulations, technical factors such as lack of uniformity in using monoclonal antibody clone type, and differences in flow cytometry methodology, processing, and data analysis 74,76 .…”
Section: Discussionmentioning
confidence: 99%